2001
DOI: 10.1016/s0921-5093(00)01519-7
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of undercooled Pb–Sn alloys

Abstract: Melt undercooling opens new solidification pathways for non-equilibrium phases and non-conventional microstructures. Several techniques, including the fluxing technique, have been developed in order to reduce nucleation sites and to produce high undercoolings for metals and alloys. In this work the fluxing technique was applied to Pb-25wt%Sn (hypoeutectic), Pb-61.9wt%Sn (eutectic) and Pb-90wt%Sn (hypereutectic) alloys to investigate the influence of the undercooling on the microstructure of these alloys. For t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 13 publications
0
7
0
3
Order By: Relevance
“…The intensive interest in these solder alloys is attributed to their low cost and unique material properties including the high superplastic properties, low melting temperature, wettability, and good electrical conductivity [2]. However, different limitations to practical applications like the strain hardening or the excessive growth of intermetallic phases at the solder-substrate joint interfaces remain, and the understanding of the microstructure of these alloys is still the subject of recent works [3][4][5]. The density investigations of the Pb-Sn eutectic by a gamma-ray absorption method revealed anomalies on the density polytherms, which were explained as transition of the quasi-eutectic melt to the micro-homogeneous state [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The intensive interest in these solder alloys is attributed to their low cost and unique material properties including the high superplastic properties, low melting temperature, wettability, and good electrical conductivity [2]. However, different limitations to practical applications like the strain hardening or the excessive growth of intermetallic phases at the solder-substrate joint interfaces remain, and the understanding of the microstructure of these alloys is still the subject of recent works [3][4][5]. The density investigations of the Pb-Sn eutectic by a gamma-ray absorption method revealed anomalies on the density polytherms, which were explained as transition of the quasi-eutectic melt to the micro-homogeneous state [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Therefore, many studies on the microstructure of various solder alloys and the intermetallic formation between solder alloys and metal films have been published. [4][5][6] However, the microstructure of an ultrasmall solder bump may be different from that of bulk solder because the geometrical structure of the under-bump metallization (UBM) volume is increased more than the solder volume with decreasing bump size in flipchip technology. Previous work 7 demonstrated that the solder surface and the UBM interface played an important role on the microstructure of the solder bump for flip-chip technology with decreasing bump size.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it is noted that the Pb -Sn alloy microstructure is unstable, and recrystallisation may take place at high temperatures or after long retention periods in the resin. 23,24 Solidification of the resin took y6 h. To monitor the recrystallisation process, a set of reference samples were prepared by mounting samples with half melting paraffin wax. The mounting temperature was y40uC and solidification time y15 min.…”
Section: Methodsmentioning
confidence: 99%